Influência de coagulantes na geração de biometano através da digestão anaeróbia de biomassa microalgácea - Moreira, Ana Beatriz Lobo (2018)
Biofuel production by anaerobic digestion of microalgae is an alternative to environmental problems and unrestrained use of fossil fuels. However, the hardest challenging stages is the recovery of microalgae biomass. One of the most common method to recovery microalgae biomass is Coagulation-Flocculation. This research aims to verify the influence of coagulants employed in the recovery of microalgae biomass in the production of biomethane. Microalgae was cultivated on five (5) photobioreactors that were inoculated with Chlorella sp. donated by the Laboratório de Saneamento (UFES) and filled with domestic sewage treatment effluent from Araçás WWTP, Vitória, Brazil. The cultivation lasted 8 (eight) days, at external environment and day/night regime with artificial aeration. In the recovery of the biomass the coagulants aluminum sulfate, cationic cassava starch and tannin were added to microalgae in doses of 80 mg/L. Biomass obtained by natural sedimentation was the negative control. Biodigestion assays were performed on AMPTS II, from Bioprocess Control (Sweden). The recovery by distinct coagulants produced heterogeneous organic composition biomass. Biomethane yield assay without hydrolysis lasted 33 days and the biomethane production was similar on biomass flocculated with starch, aluminum sulphate and by natural settling. Tannin based biomass showed a higher yield of biomethane than others (120.4 mL CH4 / g SV). The assay after alkaline pretreatment lasted 19 days and all treatments were different from each other. Cationic Starch was the biomass that presented the highest biomethane yield (107.8 mL CH4 / g SV) and the highest increase percentage in the ratio of the unpretreated biomass (98.8%). Biomethane decreasing on pretreated tannin flocculated biomass (-56.1%) and aluminum sulphate (-27.8%) suggests that coagulant, as hydrolysis itself may influence the anaerobic digestion. Finally, unpretreated tannin flocculated biomass and pretreated flocculated starch biomass showed a better biomethane yield than the other flocculated biomass and when compared to natural settling biomass without addition of any coagulant.